1986
DOI: 10.1007/bf00269257
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration by organogenesis in Glycine max

Abstract: A procedure for the regeneration of fertile plants by organogenesis from tissue cultures of soybeans, Glycine max is described. Seeds were germinated on reduced inorganic salt MS medium containing 5μM BA. Cotyledonary nodes were excised and cultured on the same medium. Presence of BA in the medium during seed germination and culture of nodal explants was required for multiple shoot and shoot-bud formation. Histological analyses established the de novo nature of shoot regeneration. Separate reduction of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
4

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 8 publications
0
46
0
4
Order By: Relevance
“…1E, F (Han et al, 2014;Ko 1999;Ko et al 1993). 이는 많은 작물의 신초발생 연구에서 BA가 매우 효과적이다는 결과와 일치하고 있다(Malik and Barwale et al, 1986;Wright et al, 1986). …”
Section: Dc)unclassified
“…1E, F (Han et al, 2014;Ko 1999;Ko et al 1993). 이는 많은 작물의 신초발생 연구에서 BA가 매우 효과적이다는 결과와 일치하고 있다(Malik and Barwale et al, 1986;Wright et al, 1986). …”
Section: Dc)unclassified
“…Carbon source (sucrose or fructose) and salt concentration (full MS, ½ MS or 1/4MS) have different effects even hormone concentration is kept constant. They further reported that seedlings germinated on water agar medium were not so responsive for shoot induction (Wright et al, 1986). BAP treatment to embryonic axes does not allow the cell to remain quiescent and cells are reprogrammed to produce multiple somatic foci (Buising et al, 1994).…”
Section: Soybean Tissue Culture Strategiesmentioning
confidence: 99%
“…Dramatic cultivar-dependent differences in the number of shoots formed per axis were noted by Barwale et al (1986a;. Wright et al, (1986aWright et al, ( , 1986b characterized de novo multiple shoot production from excised cotyledonary nodes during the period of 6 to 28 days after continuous culture on 5 |iM BAP followed on occasion by transfer to 1 jO-M BAP; proregenerative tissues were produced by 6 days. In addition, Wright et al, (1986a; and Barwale et al, (1986a; reported that BAP interfered with subsequent development and elongation of multiple shoots.…”
Section: Methods Of Increasing Transformationmentioning
confidence: 99%
“…Wright et al, (1986aWright et al, ( , 1986b characterized de novo multiple shoot production from excised cotyledonary nodes during the period of 6 to 28 days after continuous culture on 5 |iM BAP followed on occasion by transfer to 1 jO-M BAP; proregenerative tissues were produced by 6 days. In addition, Wright et al, (1986a; and Barwale et al, (1986a; reported that BAP interfered with subsequent development and elongation of multiple shoots. Wright et al (1986a) concluded, however, that continuous exposure to BAP was required for additional bud production.…”
Section: Methods Of Increasing Transformationmentioning
confidence: 99%
See 1 more Smart Citation